Revitalization of Batik Gallery as a Culture-Based Educational Tourism Destination in Promoting Batik “Sekar Ndaru” Gondang Village: Revitalisasi Galeri Batik Sebagai Destinasi Wisata Edukasi Berbasis Budaya Dalam Mempromosikan Batik “Sekar Ndaru” Desa Gondang - Winantoro , Adistin Naidzira Prameswari; Pratama, Aprilianto Arya; Tirtasari , Nur Indah; Zahrani, Tarisha Jafna Diah; Setiyawati, Enik (International Consortium of Education and Culture Research Studies, 2025)
General Background: Batik art, as a significant element of Indonesia’s intangible cultural heritage, represents the confluence of artistic expression, cultural identity, and spiritual values. Specific Background: The organization of batik festivals and preservation initiatives not only honors ancestral legacies but also serves as a strategic avenue for promoting culture-based tourism rooted in local traditions and religious harmony. Knowledge Gap: Despite the cultural richness of batik, there is insufficient integration of batik preservation efforts with tourism promotion strategies, particularly those involving the active role of youth. Aims: This study aims to highlight the multifaceted contributions of the younger generation in elevating the value of batik art through cultural promotion and preservation. Results: Young individuals have demonstrated significant influence by utilizing social media to promote batik festivals, raising public awareness about the cultural importance of local products, and embodying batik’s philosophical meanings. Their participation in creating communities of cultural enthusiasts, learning and practicing batik techniques, wearing batik in educational and governmental settings, and engaging in fashion contests as batik ambassadors underscores their active role in cultural sustainability. Novelty: The involvement of youth in batik preservation through contemporary digital and participatory channels presents a dynamic model of intergenerational cultural transmission that bridges heritage with innovation. Implications: The integration of batik art into tourism promotion strategies through youth participation offers potential for strengthening cultural appreciation, enhancing religious and cultural unity, and positioning batik as a vital element in Indonesia’s cultural tourism development. Keywords: Batik Art, Cultural Heritage, Youth Participation, Tourism Promotion, Religious Harmony Highlights: Youth engagement strengthens batik’s cultural preservation through modern platforms. Batik festivals serve as channels for promoting local wisdom and tourism. Cultural identity and spirituality are embedded in batik as a heritage symbol.